Developmental Phenotypic and Transcriptomic Effects of Exposure to Nanomolar Levels of 4-Nonylphenol, Triclosan, and Triclocarban in Zebrafish (Danio rerio) - Jessica Phillips; Alex S. Haimbaugh; Camille Akemann; Jeremiah N. Shields; Chia-Chen Wu; Danielle N. Meyer; Bridget B. Baker; Zoha Siddiqua; David K. Pitts; Tracie R. Baker (Toxics, 2022)
Triclosan, triclocarban and 4-nonylphenol are all chemicals of emerging concern found in a wide variety of consumer products that have exhibited a wide range of endocrine-disrupting effects and are present in increasing amounts in groundwater worldwide. Results of the present study indicate that exposure to these chemicals at critical developmental periods, whether long-term or short-term in duration, leads to significant mortality, morphologic, behavioral and transcriptomic effects in zebrafish (Danio rerio). These effects range from total mortality with either long- or short-term exposure at 100 and 1000 nM of triclosan, to abnormalities in uninflated swim bladder seen with long-term exposure to triclocarban and short-term exposure to 4-nonylphenol, and cardiac edema seen with short-term 4-nonylphenol exposure. Additionally, a significant number of genes involved in neurological and cardiovascular development were differentially expressed after the exposures, as well as lipid metabolism genes and metabolic pathways after exposure to each chemical. Such changes in behavior, gene expression, and pathway abnormalities caused by these three known endocrine disruptors have the potential to impact not only the local ecosystem, but human health as well.